Positive youth development through sports among urban poor youth in Subang Jaya, Malaysia - Ravichandren, Chandreshan; Abdullah, Haslinda; Zaremohzzabieh, Zeinab (Human Resource Management Academic Research Society, 2023)
Nowadays maximize youth experiences in community sports programs, especially for vulnerable and/or marginalized youth who may have limited access and opportunity to these experiences is vital. This study examined how community youth sports programs have been community-focused in developing the youth’s life skills and creating positive youth development (PYD) among urban poor youths in Subang Jaya, Malaysia. Therefore, this study was conducted using a qualitative case study approach with participants that were chosen through purposive sampling. After interviewing eight interviewees, eight themes emerged using MAXQDA 20.0 statistics software. The study findings showed that a significant PYD that is measured through 8Cs of PYD based on Malaysian Youth Policy and the birth of the eighth C in the youths through the sports-based youth development programs. The study was able to capture and highlight the significant changes in the youths’ lives.